A test of the effects of the equine maternal pheromone on the clinical and ethological parameters of equines undergoing hoof trimming - Alves de Paula, Renata [UNESP] (2019)
“Pheromonal therapy” has been promoted as a promising alternative therapy to improve the human-animal relationship and to reduce behavioral reactions to stressful stimuli. This placebo-controlled double blind study evaluated the use of a synthetic equine maternal pheromone (EMP) in animals undergoing hoof trimming for effects on behaviors and autonomous nervous system responses. Twenty foals (14 females and 6 males) with an average age of 24 months were divided into two experimental groups (A and B); one group receiving treatment with EMP and the other receiving placebo (excipient without the active ingredient). The parameters analyzed were heart rate (HR), respiratory rate, blood sugar levels, heart rate variability and behavioral reactions. There were no statistically significant differences in the HR, respiratory rate, and blood sugar levels when comparing the EMP and placebo groups. The heart rate variability indexes (minimum HR, average HR, maximum HR, NN, SDNN, RMSSD, and PNN50) also were not statistically significantly different when comparing the groups before, during, and after trimming. We also found no behavioral changes during the procedure of hoof trimming associated with the use of synthetic pheromonal analogues. This study provided no evidence for the effectiveness of synthetic pheromonal analogues to aid in the process of hoof trimming.